Gender Differences in the Relationship between Maladaptive Behaviors and Post-Traumatic Stress Disorder. A Study on 900 L’ Aquila 2009 Earthquake Survivors - Dell'Osso, Liliana; Carmassi, Claudia; Stratta, Paolo; Massimetti, Gabriele; Akiskal, Kareen K.; Akiskal, Hagop S.; Maremmani, Icro (Frontiers in Psychiatry, 2013)
Background: Post-traumatic stress disorder (PTSD) represents one of the most frequently psychiatric sequelae to earthquake exposure. Increasing evidence suggests the onset of maladaptive behaviors among veterans and adolescents with PTSD, with specific gender differences emerging in the latter. Aims of the present study were to investigate the relationships between maladaptive behaviours and PTSD in earthquake survivors, besides the gender differences in the type and prevalence of maladaptive behaviours and their association with PTSD. Methods: 900 residents of the town of L’Aquila who experienced the earthquake of April 6th 2009 (Richter Magnitude 6.3) were assessed by means of the Trauma and Loss Spectrum Self Report (TALS-SR). Results: Significantly higher maladaptive behaviour prevalence rates were found among subjects with PTSD. A statistically significant association was found between male gender and the presence of at least one maladaptive behaviour among PTSD survivors. In the latter, significant correlations emerged between maladaptive coping and symptoms of re-experiencing, avoidance and numbing and arousal in women, while only between maladaptive coping and avoidance and numbing in men. Conclusions: Our results show high rates of maladaptive behaviours among earthquake survivors with PTSD suggesting a greater severity among men. Interestingly, post-traumatic stress symptomatology appears to be a better correlate of these behaviours among women than among men, suggesting the need for further studies based on a gender approach.